THE PRIORITIES OF ENGLISH PRONUNCIATION ELEMENTS FOR INDONESIAN JUNIOR HIGH SCHOOL STUDENTS - Lucky Rahayu Nurjamin (Institut Pendidikan Indonesia Garut, 2020)
The unclear English pronunciation elements taught to Indonesian junior high school students may cause many different impacts related to the suitable elements of English pronunciation in EFL context. This phenomenon triggers this study to address the relevant elements of English pronunciation for Indonesian junior high school students. In this study, qualitative approach employing library research is chosen as the research methodology. The data are taken from books and journals related to teaching and learning English pronunciation in EFL context, particularly in Indonesian context. As a result, the study reveals that sounds, stress, and intonation are the core competence of English pronunciation that should be taught for junior high school students in Indonesian context.Â